Środowisko pracy a wypalenie zawodowe – analiza wzajemnych relacji na przykładzie badań reprezentantów różnych obszarów aktywności - Lubrańska, Anna (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
The phenomenon of burnout is linked to a close relationship with another human being. According to classical views, burnout is described from the perspective of professions involving “service”. The traditional take on the phenomenon raises a question of whether in today’s multidimensional dynamic professional world the phenomenon of burnout can affect other professions? This study is an attempt to verify the above issue. The problem in question has been investigated in reference to D. Predigerʼs concept. The study involved different career groups, representatives of the four spheres of activity Data–Ideas, People–Things.